Strategies for promoting sustainable hospitality and tourism services - Korstanje, Maximiliano; George, Babu P.; Nedelea, Alexandru, 1971- (Business Science Reference, an imprint of IGI Global, 2020)
"This book discusses interdisciplinary perspectives in the areas of global tourism and highlights cultural boundaries of strategic knowledge management through case studies"--